THE ROLE OF SULFIDE ANION IN THE DEVELOPMENT OF OXIDATIVE STRESS IN THE LIVER UNDER CONDITIONS OF CHRONIC ALCOHOLIC HEPATITIS - Mykytenko, A.O.; Akimov, O.Ye.; Yeroshenko, G.A.; Neporada, K.S. (World of Medicine and Biology, 2022)
The pathogenesis of alcoholic hepatitis is multifactorial and is the final result of a complex interaction of ethanol metabolism, inflammation and immunological reactions. The molecular mechanisms of H2S action in alcoholic hepatitis have not been sufficiently studied, and its protective role has not been proven. The experiments were carried out on 30 white, sexually mature outbred male rats, weighing 180–220 g. The animals were divided into 2 groups: І – control (n=6); ІІ group – animals on which we simulated alcoholic hepatitis. In the homogenate of the liver of rats, the activity of superoxide dismutase and catalase, the concentration of malondialdehyde and oxidatively modified proteins, sulfide anion concentration and the production of superoxide anion were determined. A decrease in the concentration of sulfide anion against the background of an increase in the activity of superoxide dismutase and the presence of an inversely proportional strong correlation between them indicates the effect of alcohol on the thioredoxin system, namely, on the increase of expression of a protein that interacts with thioredoxin, stimulating the reaction of the latter with reactive oxygen species. Chronic alcohol intoxication leads to the development of oxidative stress in the liver of rats due to an increase in the production of reactive oxygen species. The decrease in the concentration of sulfide anion on the 28th day of the experiment is connected with its usage as an antioxidant.